Nihilism and Technoscience: metaphysics in the realm of machines - Fernández Mateo, Joaquín (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
The aim of this paper is to develop an in-depth understanding of the metaphysical transformations that have enabled technological acceleration and to sketch a viable way forward. Faced with way of revealing of the essence of technology, the elaboration of an ontological thought makes it possible to trace an ontological difference that transcends the reduction of the world to an entity-object. Unlike a forced and violent expression that requires an industrial energetic structure for its maintenance and a constant flow of usable energy, ontological thought takes care of being, contemplates and respects it, renouncing to turn reality into a mere object of use and domination.